2019
DOI: 10.1038/s41416-019-0442-5
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 expression predicts peritoneal recurrence after curative resection of primary colon cancer

Abstract: BACKGROUND: The aim of this study was to clarify whether a cancer stem cell marker could be an indicator of post-operative peritoneal recurrence of colon cancer. METHODS: Expression of four putative markers (CD133, CD44 variant 6, aldehyde dehydrogenase-1 and leucine-rich repeating G-protein-coupled receptor-5 (LGR5)) was evaluated immunohistochemically in primary tumour samples from 292 patients who underwent curative resection for non-metastasised pT4 colon cancer at the University of Tokyo Hospital between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Moreover, a different study has scored LGR5 expression in both the epithelium and stroma of the tumor 30. The current study demonstrated that LGR5 was significantly expressed in CC as compared with adjacent normal mucosa, which was comparable with the previous results 31,32. This observation was consistent with the role of LGR5 in carcinogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a different study has scored LGR5 expression in both the epithelium and stroma of the tumor 30. The current study demonstrated that LGR5 was significantly expressed in CC as compared with adjacent normal mucosa, which was comparable with the previous results 31,32. This observation was consistent with the role of LGR5 in carcinogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The reasons for termination of this clinical trial have not been made known publicly. Most recently Nagata et al [26] found that a negative LGR5 expression was a significant predictor of peritoneal recurrence in patients with pT4 colon cancer, while Sato et al [27] documented that there was a significant difference in OS between the LGR5-positive group and LGR5-negative group, with a Cox proportional hazards models revealing the LGR5-positive group as having a better OS.…”
Section: Discussionmentioning
confidence: 99%
“…These are involved in chemotherapy resistance and malignant tumor metastasis. 4,5 In addition, the OCT4, SOX2, and Nanog genes are overexpressed in CSCs and play a dominant role in maintaining and inducing pluripotency. 6 Thus, CSCs exhibit a renewable and differentiated ability leading to tumor growth, metastasis, chemotherapy resistance, and cancer relapse.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Accumulating evidence demonstrates that there is a small subpopulation of cancer stem-like cells (CSCs) in CRC with characteristics similar to embryonic stem cells (ESCs), which are associated with the progression and relapse of CRC. , CSC-related markers including aldehyde dehydrogenase (ALDH), CD44, CD133, and leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5) have been identified in CRC. These are involved in chemotherapy resistance and malignant tumor metastasis. , In addition, the OCT4, SOX2, and Nanog genes are overexpressed in CSCs and play a dominant role in maintaining and inducing pluripotency . Thus, CSCs exhibit a renewable and differentiated ability leading to tumor growth, metastasis, chemotherapy resistance, and cancer relapse. , Therefore, targeting the CSCs is a novel approach in addressing cancer progression and prognosis.…”
Section: Introductionmentioning
confidence: 99%